Correction of Steady-State Conditions of Electrical Power Engineering System with Given Active Power and Arguments for Complex Voltages in Station Units - K. V. Khachatryan (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
A new method concerning correction of steady-state conditions of electrical power engineering system while changing initial information relative to active parameters of electrical power engineering system is proposed in the paper.